Guaianolide and Pseudoguaianolide from Pulicaria laciniata - ABERKANE*, M.C.; DIBI, A.; HABA, H.; BENKHALED, M.; BENKOUIDER, A.; MOKHTARI, M.; MOSSET, P.; PALE!, P. (Asian Journal of Chemistry, 2010)
The first study of the aerial parts of Pulicaria laciniata afforded one guaianolide, one pseudoguaianolide and a β-sitosterol. The structures of the three compounds were elucidated by spectroscopic techniques including 2D NMR experiments.